Potensi Pengembangan Wilayah Sumber Bibit Sapi Bali Rakyat di Kecamatan Tinanggea, Kabupaten Konawe Selatan - M. Abadi; L. O. Nafiu; T. Saili; L. Yunus; Gerhana (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2025)
The development of Bali cattle faces challenges, including increasingly limited land for both livestockfarming and forage crops. This research aims to assess the potential of Tinanggea District, SouthKonawe Regency, as a development area for Bali cattle breeding. The field study was conducted fromFebruary to March 2023. The research location was selected through purposive sampling, specifically inTinanggea District, which serves as one of the central regions for Bali cattle seed sources. Respondentswere determined using a census method, involving a total of 716 livestock farmers. To analyze thecollected data, several analytical approaches were employed, including economic density, farm density,area density, and the Capacity for Increasing Bali Cattle Population (CIBCP). The analysis resultsrevealed that economic density falls into the moderate category with a value of 86.09 Livestock Units(LU) per 1.000 people. Farm density is also categorized as moderate, with a value of 0.27 LU per hectare,while area density is considered low, with a value of 6.27 LU per square kilometer. The combinationof livestock density identified as a Development Area (DA) was found in the economic–farm densitycombination, while the Distribution and Development Area (DDA) was identified in both the economic–area and farm–area combinations. The effective CIBCP value in Tinanggea District still shows potentialfor an increase of up to 293 LU. At the village level, the effective CIBCP values in Tinanggea Districtcan be grouped into three development categories: high (4 villages), moderate (3 villages), and low (17villages). Roraya Village has the highest effective CIBCP value, amounting to 116 LU, whereas the villagewith the lowest value is Telutu Jaya, which has an effective CIBCP of -193 LU